2023
DOI: 10.1186/s12888-023-05165-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between the rs6313 polymorphism in the 5-HTR2A gene and the efficacy of antipsychotic drugs

Yulong Wang,
Xingru Tan,
Zhoufangyuan Chen
et al.

Abstract: Background Prescribing the optimal antipsychotic treatment to schizophrenia is very important as it is well established that patients have different sensitivity to the available antipsychotic drugs. The genotype of the HTR2A T102C (rs6313) polymorphism has been suggested to affect the efficacy of antipsychotic drugs, but the results of different studies have been inconsistent Methods In this study, a meta-analysis was used to ascertain the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…However, Sujitha et al have revealed an rs6313 association with schizophrenia in the Tamil-speaking population of South India [89]. It is interesting that Wang et al have shown that polymorphism can affect antipsychotic drug susceptibility depending on ethnicity [90]. Taken as a compound, this data reflects the influence of environmental and geographical factors on genes and acknowledges the relevance of a study of genetic alleles' frequency and association in various populations.…”
Section: Europeanmentioning
confidence: 93%
“…However, Sujitha et al have revealed an rs6313 association with schizophrenia in the Tamil-speaking population of South India [89]. It is interesting that Wang et al have shown that polymorphism can affect antipsychotic drug susceptibility depending on ethnicity [90]. Taken as a compound, this data reflects the influence of environmental and geographical factors on genes and acknowledges the relevance of a study of genetic alleles' frequency and association in various populations.…”
Section: Europeanmentioning
confidence: 93%